Wouldn't Take Nothing for My Journey Now - Angelou, Maya (Time Warner Books, 1993)
The woman warrior who is armed with wit and courage will be among the first to celebrate victory' says Maya Angelou, bestselling author of I KNOW WHY THE CAGED BIRD SINGS and one of our best-loved writers. Here she writes about family, argues for spirit and grace, insists on the importance of laughter and style and reflects on brutality and crime. She has the courage to say the unfashionable: 'virtue, purity, temperance, goodness, worth or even moderation...we must return them to a vigorous role in our lives', and the wit to call for them with humour. As lessons in living, they are a unique inspiration.
Keywords: Biography and Autobiography; Non-Fiction